The effect of SAMA control on the financial performance of Saudi banks from the perspective of workers in general supervision of banks - Alshareff, Amal Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the impact (influence) of SAMA's control on the financial performance of Saudi banks from the perspective (viewpoint) of the employees responsible for the bank's general control. The study adopted the analytical descriptive approach. The questionnaire was used as a data collection tool applied to a random sample composed of (120) employees. The study concluded several findings, the most important of which is the impact of control through the regulations and instructions in the Saudi banks on financial performance. There is also an effect of control through the inspections in the Saudi banks on financial performance, in addition to the effect of control through data and periodic statements in Saudi banks on financial performance.The study recommended several recommendations, the most important of which is the need to continue banking reforms to keep up with the current global developments witnessed by all banks in the Kingdom, in addition to the need to provide adequate systems and means to assess and measure the various risks encountered by banks and increase attention to prepare and organize courses and training programs in the field of control.
Keywords: public control; financial performance; Saudi Monetary Agency